Social, Cultural and Political India In the Novels of Rohinton Mistry: Exploring the Social, Cultural, and Political Realities of Parsis in India through Rohinton Mistry's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Rohinton Mistry‘s works seeks to evolve a vision that involves both thecommunity-centred existence of the Parsis and their involvement with the widernational framework. This paper mainly focuses about social, cultural andpolitical facts in the novels of Rohinton mistry in India. His novels areconcerned with the experience of the Parsi in India.